Fiber-reinforced thermoplastic resin substrate

The fiber-reinforced thermoplastic resin base material with specified molecular weight, ash content, and carboxyl group content in polyphenylene sulfide resin addresses gelation issues, enhancing mechanical properties and stability, achieving 90° bending strength of 130 to 200 MPa.

JP7605106B2Active Publication Date: 2024-12-24TORAY INDUSTRIES INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021518829
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-18
Filing Date
2021-03-16
Publication Date
2024-12-24
Estimated Expiration
2041-03-16

AI Technical Summary

Technical Problem

Conventional methods for producing carbon fiber-reinforced polyphenylene sulfide (PPS) resin materials suffer from issues such as gelation during high-temperature processing, lack of specification on molecular weight, carboxyl group content, and ash content, leading to instability and inadequate mechanical properties.

Method used

A fiber-reinforced thermoplastic resin base material is developed with polyphenylene sulfide resin having a weight average molecular weight of 75,000 to 150,000, ash content of 0.001% to 0.30% by weight, and carboxyl group content of 5 to 25 μmol/g, along with specific fiber volume content and arrangement, to enhance mechanical properties.

Benefits of technology

The material achieves improved mechanical properties, including 90° bending strength of 130 to 200 MPa, and better adhesion and toughness, addressing the limitations of previous methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605106000001
    Figure 0007605106000001
  • Figure 0007605106000002
    Figure 0007605106000002
  • Figure 0007605106000003
    Figure 0007605106000003
Patent Text Reader

Abstract

The objective of the present invention is to provide a fiber-reinforced thermoplastic resin substrate having excellent mechanical characteristics. In order to achieve the objective, a fiber-reinforced thermoplastic resin substrate according to the present invention has the following configuration. That is, provided is a fiber-reinforced thermoplastic resin substrate in which a plurality of continuous reinforced fibers are impregnated with a polyphenylene sulfide resin, wherein the weight-average molecular weight of the polyphenylene sulfide resin is 75000-150000, and the ash content of the polyphenylene sulfide resin is 0.001-0.30 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fiber-reinforced thermoplastic resin substrate. [Background technology]

[0002] Fiber-reinforced thermoplastic resin substrates, in which multiple continuous reinforcing fibers are impregnated with thermoplastic resin, are not only lightweight, but also have superior toughness, weldability, and recyclability compared to fiber-reinforced thermoplastic resin substrates using thermosetting resins, and are therefore being widely deployed in a variety of applications, including transportation equipment such as aircraft and automobiles, and sports, electrical, and electronic parts. In recent years, in addition to the mechanical strength and lightweight properties that were previously the added value of CFRTP (carbon fiber reinforced thermoplastic resin) intermediate substrates, high added value such as high heat resistance, low water absorption, high toughness, and moldability has also been required, and there is a strong demand for technological development of high-performance CFRTP intermediate substrates, mainly for aircraft and automobile applications.

[0003] Polyphenylene sulfide (hereinafter sometimes abbreviated as PPS) resin is a crystalline thermoplastic resin with excellent heat resistance and chemical resistance, and is also attracting attention as a matrix resin for composite materials. However, conventional PPS resin is essentially a brittle material with low toughness, and in the case of fibers such as carbon fiber that barely expand when heated, the residual stress during molding is large, and even a slight disturbance in the fiber arrangement can cause the molded product to bend or crack, resulting in insufficient composite properties such as bending strength and interlaminar shear strength.

[0004] Patent Document 1 discloses a method for producing a carbon fiber-reinforced PPS substrate having excellent mechanical properties by impregnating the substrate with uncrosslinked PPS resin, heating the substrate at 300 to 360° C. for a specific period of time, and carrying out a thermal crosslinking treatment.

[0005] Furthermore, Patent Document 2 discloses a method for producing a carbon fiber-reinforced PPS substrate having excellent mechanical properties by using a PPS resin that has been oxidatively crosslinked in the atmosphere.

[0006] Furthermore, Patent Document 3 discloses a method for producing a carbon fiber-reinforced PPS substrate having excellent mechanical properties by using a resin composition of a PPS resin oxidatively crosslinked in the atmosphere and a high-molecular-weight PPS resin.

[0007] Furthermore, Patent Document 4 discloses a method for producing a short carbon fiber reinforced PPS substrate having excellent mechanical properties by using a resin composition of a high molecular weight PPS resin. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 1477262 [Patent Document 2] Japanese Patent Application Publication No. 2-180934 [Patent Document 3] Japanese Patent Application Publication No. 3-292335 [Patent Document 4] Japanese Patent Application Publication No. 9-25346 Summary of the Invention [Problem to be solved by the invention]

[0009] The method proposed in Patent Document 1 is said to produce a carbon fiber reinforced PPS substrate with excellent mechanical properties, but a carbon fiber reinforced PPS substrate with even better mechanical properties is desired. In addition, since the PPS resin is heated to high temperatures during production, gelation is likely to occur in the PPS resin, which reduces the stability of the process. Furthermore, there is no specific disclosure of the molecular weight, carboxyl group content, and ash content of the PPS resin.

[0010] The method proposed in Patent Document 2 has the problem that gelled matter is likely to occur in the PPS resin, which reduces the stability of the manufacturing process and the mechanical properties of the molded product. Furthermore, there is no specific disclosure of the molecular weight, carboxyl group content, and ash content of the PPS resin.

[0011] The method proposed in Patent Document 3 has problems in that the production process is complicated and gelled matter is likely to occur in the PPS resin, resulting in reduced process stability during production and reduced mechanical properties of the molded product.

[0012] Although the method proposed in Patent Document 4 is said to produce a short carbon fiber reinforced PPS substrate with excellent mechanical properties, a carbon fiber reinforced PPS substrate with even better mechanical properties is desired. Furthermore, there is no specific disclosure of the molecular weight, carboxyl group content, and ash content of the PPS resin.

[0013] Thus, the mechanical properties of fiber-reinforced PPS substrates produced using conventional techniques were insufficient. The present invention provides a fiber-reinforced thermoplastic resin substrate having excellent mechanical properties. [Means for solving the problem]

[0014] (1) A fiber-reinforced thermoplastic resin substrate in which a plurality of continuous reinforcing fibers are impregnated with polyphenylene sulfide resin, the polyphenylene sulfide resin having a weight average molecular weight of 75,000 or more and 150,000 or less, and an ash content of the polyphenylene sulfide resin being 0.001% by weight or more and 0.30% by weight or less. (2) The fiber-reinforced thermoplastic resin substrate according to (1) above, wherein the polyphenylene sulfide resin has an ash content of 0.001% by weight or more and 0.25% by weight or less. (3) The fiber-reinforced thermoplastic resin substrate according to (1) or (2), wherein the polyphenylene sulfide resin has a carboxyl group content of 5 μmol / g or more and 25 μmol / g or less. (4) A fiber-reinforced thermoplastic resin substrate according to any one of (1) to (3), having a fiber volume content of 20 to 65 volume %. (5) The fiber-reinforced thermoplastic resin substrate according to any one of (1) to (4), having a 90° bending strength of 130 to 200 MPa as measured in a 90° bending test of a molded piece in accordance with ASTM D790. Effect of the Invention

[0015] According to the present invention, a fiber-reinforced thermoplastic resin substrate having excellent mechanical properties can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, an embodiment of the present invention will be described in detail.

[0017] <Reinforced fiber> The type of reinforcing fiber is not particularly limited, and examples include carbon fiber, metal fiber, organic fiber, and inorganic fiber. Two or more of these may be used. By using carbon fiber as the reinforcing fiber, a fiber-reinforced thermoplastic resin substrate that is lightweight yet has high mechanical properties can be obtained.

[0018] Examples of carbon fibers include polyacrylonitrile (PAN)-based carbon fibers made from PAN fibers, pitch-based carbon fibers made from petroleum tar or petroleum pitch, cellulose-based carbon fibers made from viscose rayon or cellulose acetate, vapor-grown carbon fibers made from hydrocarbons, graphitized fibers of these, etc. Among these carbon fibers, PAN-based carbon fibers are preferably used because of their excellent balance between strength and elastic modulus.

[0019] Examples of metal fibers include fibers made of metals such as iron, gold, silver, copper, aluminum, brass, and stainless steel.

[0020] Examples of organic fibers include fibers made of organic materials such as aramid, polybenzoxazole (PBO), polyphenylene sulfide, polyester, polyamide, and polyethylene. Examples of aramid fibers include para-aramid fibers, which are excellent in strength and elastic modulus, and meta-aramid fibers, which are excellent in flame retardancy and long-term heat resistance. Examples of para-aramid fibers include polyparaphenylene terephthalamide fibers and copolyparaphenylene-3,4'-oxydiphenylene terephthalamide fibers, and examples of meta-aramid fibers include polymetaphenylene isophthalamide fibers. As aramid fibers, para-aramid fibers, which have a higher elastic modulus than meta-aramid fibers, are preferably used.

[0021] Examples of inorganic fibers include fibers made of inorganic materials such as glass, basalt, silicon carbide, and silicon nitride. Examples of glass fibers include E-glass fiber (for electrical use), C-glass fiber (for corrosion resistance), S-glass fiber, and T-glass fiber (high strength and high elastic modulus). Basalt fiber is a fiber made from basalt, a mineral, and has very high heat resistance. Basalt generally contains 9 to 25% by weight of FeO or FeO2, which is an iron compound, and 1 to 6% by weight of TiO or TiO2, which is a titanium compound, but it is also possible to increase the amount of these components in a molten state and make the fiber.

[0022] Since the fiber-reinforced thermoplastic resin substrate of the present invention is often expected to serve as a reinforcing material, it is desirable for it to exhibit high mechanical properties, and in order to exhibit high mechanical properties, it is preferable that the reinforcing fibers contain carbon fibers.

[0023] In the fiber-reinforced thermoplastic resin substrate of the present invention, the reinforcing fiber is usually composed of one or more reinforcing fiber bundles each formed by bundling a large number of single fibers. The total number of filaments (the number of single fibers) of the reinforcing fiber when one or more reinforcing fiber bundles are arranged is preferably 1,000 to 2,000,000. From the viewpoint of productivity, the total number of filaments of the reinforcing fiber is more preferably 1,000 to 1,000,000, further preferably 1,000 to 600,000, and particularly preferably 1,000 to 300,000. When the total number of filaments of the reinforcing fiber is 1,000 or more, the productivity is easily improved. In addition, when the total number of filaments of the reinforcing fiber is 2,00,000 or less, the dispersibility and the handleability are easily improved.

[0024] In the present invention, one reinforcing fiber bundle is preferably formed by bundling 1,000 to 50,000 reinforcing monofilaments each having an average diameter of 5 to 10 μm.

[0025] The fiber-reinforced thermoplastic resin substrate of the present invention is characterized in that the thermoplastic resin impregnated into a plurality of continuous reinforcing fibers is a polyphenylene sulfide resin described below.

[0026] In the present invention, the continuous reinforcing fiber refers to a reinforcing fiber that is not interrupted. Examples of the form and arrangement of the reinforcing fiber include those that are aligned in one direction, woven fabric (cloth), knitted fabric, braided cord, tow, etc. Among them, it is preferable that the reinforcing fiber is aligned in one direction, since the mechanical properties in a specific direction can be efficiently improved.

[0027] <Polyphenylene sulfide resin> The polyphenylene sulfide resin (PPS resin) used in the present invention is a polymer having a repeating unit represented by the following structural formula.

[0028] [ka]

[0029] From the viewpoint of heat resistance, the PPS resin preferably contains 70 mol % or more, and more preferably 90 mol % or more, of the repeating units represented by the above structural formula. In addition, the PPS resin may be composed of repeating units having the following structure, etc., at about less than 30 mol % of the repeating units.

[0030] [ka]

[0031] A PPS resin partially having such a structure has a lower melting point, which is advantageous in terms of moldability.

[0032] It is important that the weight average molecular weight of the PPS resin used in the present invention is 75,000 or more and 150,000 or less. The lower limit of the weight average molecular weight of the PPS resin is 75,000, preferably 76,000, and more preferably 77,000. The upper limit of the weight average molecular weight of the PPS resin is 150,000, preferably 130,000, and more preferably 100,000. When the weight average molecular weight of the PPS resin is in the above preferred range, a fiber-reinforced thermoplastic resin substrate having better mechanical properties tends to be obtained. When the weight average molecular weight is less than 75,000, the mechanical properties of the PPS resin itself tend to decrease, and the adhesion between the PPS resin and the reinforcing fiber also tends to decrease, so that the mechanical properties of the fiber-reinforced thermoplastic resin substrate tend to decrease. On the other hand, when the weight average molecular weight of the PPS resin is greater than 150,000, the melt viscosity becomes significantly large, so that the impregnation with the reinforcing fiber decreases, and there is a tendency that a fiber-reinforced thermoplastic resin substrate impregnated with the PPS resin well cannot be obtained.

[0033] The weight average molecular weight in the present invention is a value calculated in terms of polystyrene using a gel permeation chromatography (GPC) manufactured by Senshu Scientific Co., Ltd., as described later.

[0034] In the fiber reinforced thermoplastic resin substrate of the present invention, it is important that the ash content of the PPS resin is 0.001% by weight or more and 0.30% by weight or less. The upper limit of the ash content is 0.30% by weight, preferably 0.25% by weight, more preferably 0.20% by weight or less, and even more preferably 0.10% by weight. When the ash content of the PPS resin is within the above preferred range, a fiber reinforced thermoplastic resin substrate having better mechanical properties tends to be obtained. When the ash content of the PPS resin is less than 0.001% by weight, the toughness of the PPS resin itself and the adhesion to the reinforcing fibers tend to decrease. On the other hand, when the ash content of the PPS resin is more than 0.30% by weight, the mechanical properties of the obtained fiber reinforced thermoplastic resin substrate decrease, which is not preferable. As a means for setting the ash content within the above range, for example, a method of performing an acid treatment or a hot water treatment in the post-treatment step of the method for producing a PPS resin described later can be mentioned. The ash content of the PPS resin is measured by the method described later.

[0035] In the fiber-reinforced thermoplastic resin substrate of the present invention, from the viewpoint of improving adhesion with the reinforcing fibers, the carboxyl group content of the PPS resin is preferably 5 μmol / g or more and 25 μmol / g or less. The lower limit of the carboxyl group content is preferably 5 μmol / g, more preferably 8 μmol / g, and even more preferably 10 μmol / g. The upper limit of the carboxyl group content is preferably 25 μmol / g, more preferably 20 μmol / g. When the carboxyl group content of the PPS resin is 5 μmol / g or more, the interaction and adhesiveness with the reinforcing fibers tend to be further improved. On the other hand, when the carboxyl group content of the PPS resin is 25 μmol / g or less, the volatile content in the processing step can be further reduced. The carboxyl group content of the PPS resin is a value calculated using a Fourier transform infrared spectrometer (FT-IR).

[0036] Examples of methods for introducing carboxyl groups into a PPS resin include a method of copolymerizing a polyhalogenated aromatic compound containing a carboxyl group, and a method of adding a compound containing a carboxyl group and / or a carboxylic anhydride group, such as maleic anhydride or sorbic acid, and reacting the compound with the PPS resin while melt-kneading the compound.

[0037] The crystallization temperature of the PPS resin used in the present invention is preferably 190°C or more and 215°C or less. The lower limit of the crystallization temperature of the PPS resin is preferably 190°C, more preferably 200°C. The upper limit of the crystallization temperature of the PPS resin is preferably 215°C, more preferably 210°C. When the crystallization temperature of the PPS resin is in the above range, a fiber-reinforced thermoplastic resin substrate having better mechanical properties and heat-welding properties tends to be obtained. In addition, the crystallization temperature of the present invention is a value obtained by measuring the thermal properties of the obtained polymer in a nitrogen atmosphere using a differential scanning calorimeter (Q200 manufactured by TA Instruments) as described later, unless otherwise specified. As a means for setting the crystallization temperature of the PPS resin in the above range, for example, a method of performing acid treatment or hot water treatment in a post-treatment step of the method for producing a PPS resin described later can be mentioned.

[0038] An example of a method for producing the PPS resin used in the present invention will be described below, but the method is not limited to the one described below as long as the PPS resin having the above structure can be obtained.

[0039] First, the details of the polyhalogenated aromatic compound, the sulfidizing agent, the polymerization solvent, the molecular weight regulator, the polymerization aid and the polymerization stabilizer used in the method for producing the PPS resin will be described.

[0040] [Polyhalogenated aromatic compounds] A polyhalogenated aromatic compound refers to a compound having two or more halogen atoms in one molecule. Specific examples include polyhalogenated aromatic compounds such as p-dichlorobenzene, m-dichlorobenzene, o-dichlorobenzene, 1,3,5-trichlorobenzene, 1,2,4-trichlorobenzene, 1,2,4,5-tetrachlorobenzene, hexachlorobenzene, 2,5-dichlorotoluene, 2,5-dichloro-p-xylene, 1,4-dibromobenzene, 1,4-diiodobenzene, and 1-methoxy-2,5-dichlorobenzene. Among them, p-dichlorobenzene is preferred. In addition, for the purpose of introducing a carboxyl group, it is also one of the preferred embodiments to use a carboxyl group-containing dihalogenated aromatic compound such as 2,4-dichlorobenzoic acid, 2,5-dichlorobenzoic acid, 2,6-dichlorobenzoic acid, and 3,5-dichlorobenzoic acid, and a mixture thereof, as a copolymerization monomer. In addition, it is also possible to combine two or more different polyhalogenated aromatic compounds to form a copolymer. As such a copolymer, a copolymer containing a p-dihalogenated aromatic compound as a main component is preferable.

[0041] In order to obtain a PPS resin having a viscosity suitable for processing, the amount of the polyhalogenated aromatic compound used is preferably 0.9 to 2.0 mol, more preferably 0.95 to 1.5 mol, and even more preferably 1.005 to 1.2 mol, per mol of the sulfidizing agent.

[0042] [Sulfidizing agent] The sulfidizing agent includes alkali metal sulfides, alkali metal hydrosulfides, and hydrogen sulfide.

[0043] Specific examples of alkali metal sulfides include lithium sulfide, sodium sulfide, potassium sulfide, rubidium sulfide, cesium sulfide, and mixtures of two or more of these, with sodium sulfide being preferred. These alkali metal sulfides can be used as hydrates or aqueous mixtures, or in the anhydrous form.

[0044] Specific examples of the alkali metal hydrosulfide include sodium hydrosulfide, potassium hydrosulfide, lithium hydrosulfide, rubidium hydrosulfide, cesium hydrosulfide, and mixtures of two or more of these, with sodium hydrosulfide being preferred. These alkali metal hydrosulfides can be used as hydrates or aqueous mixtures, or in the anhydrous form.

[0045] In addition, an alkali metal sulfide prepared in situ in the reaction system from an alkali metal hydrosulfide and an alkali metal hydroxide can also be used. Alternatively, an alkali metal sulfide can be prepared from an alkali metal hydrosulfide and an alkali metal hydroxide, and then transferred to a polymerization tank for use.

[0046] Alternatively, an alkali metal sulfide prepared in situ in the reaction system from an alkali metal hydroxide such as lithium hydroxide or sodium hydroxide and hydrogen sulfide can be used.Alkaline metal sulfides can be prepared from an alkali metal hydroxide such as lithium hydroxide or sodium hydroxide and hydrogen sulfide, and then transferred to a polymerization tank for use.

[0047] When a part of the sulfidizing agent is lost before the start of the polymerization reaction due to a dehydration operation or the like, the amount of the charged sulfidizing agent means the remaining amount obtained by subtracting the lost amount from the actual charged amount.

[0048] It is also possible to use an alkali metal hydroxide and / or an alkaline earth metal hydroxide together with the sulfidizing agent.Specific examples of the alkali metal hydroxide include, for example, sodium hydroxide, potassium hydroxide, lithium hydroxide, rubidium hydroxide, cesium hydroxide, and mixtures of two or more of these.Specific examples of the alkaline earth metal hydroxide include, for example, calcium hydroxide, strontium hydroxide, barium hydroxide, etc., and among these, sodium hydroxide is preferably used.

[0049] When an alkali metal hydrosulfide is used as the sulfidizing agent, it is particularly preferred to use an alkali metal hydroxide at the same time. In such a case, the amount of the alkali metal hydroxide used is preferably 0.95 to 1.20 mol, more preferably 1.00 to 1.15 mol, and even more preferably 1.005 to 1.100 mol, per mol of the alkali metal hydrosulfide.

[0050] [Polymerization solvent] As the polymerization solvent, it is preferable to use an organic polar solvent. Specific examples include N-alkylpyrrolidones such as N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone, caprolactams such as N-methyl-ε-caprolactam, aprotic organic solvents such as 1,3-dimethyl-2-imidazolidinone, N,N-dimethylacetamide, N,N-dimethylformamide, hexamethylphosphoric triamide, dimethylsulfone, and tetramethylene sulfoxide, and mixtures thereof, all of which are preferably used because of their high reaction stability. Among these, N-methyl-2-pyrrolidone (hereinafter sometimes abbreviated as NMP) is particularly preferably used.

[0051] The amount of the organic polar solvent used is preferably 2.0 to 10 mol, more preferably 2.25 to 6.0 mol, and even more preferably 2.5 to 5.5 mol, per mol of the sulfidizing agent.

[0052] [Molecular weight regulator] A monohalogen compound (not necessarily an aromatic compound) can be used in combination with the polyhalogenated aromatic compound in order to form terminals in the resulting PPS resin or to adjust the polymerization reaction or molecular weight, etc. That is, in the present invention, a monohalogen compound may be used as a molecular weight regulator.

[0053] [Polymerization aid] In order to obtain a PPS resin with a relatively high degree of polymerization in a short time, it is also a preferred embodiment to use a polymerization aid. Here, the polymerization aid means a substance that has the effect of increasing the viscosity of the resulting PPS resin. Specific examples of such polymerization aids include organic carboxylates, water, alkali metal chlorides, organic sulfonates, alkali metal sulfates, alkaline earth metal oxides, alkali metal phosphates, and alkaline earth metal phosphates. These can be used alone or in combination of two or more. Among these, organic carboxylates, water, and alkali metal chlorides are preferred. As the organic carboxylates, alkali metal carboxylates are preferred. As the alkali metal chlorides, lithium chloride is preferred.

[0054] The alkali metal carboxylate is a compound represented by the general formula R(COOM)n (wherein R is an alkyl group, a cycloalkyl group, an aryl group, an alkylaryl group, or an arylalkyl group having 1 to 20 carbon atoms. M is an alkali metal selected from lithium, sodium, potassium, rubidium, and cesium. n is an integer of 1 to 3). The alkali metal carboxylate can also be used as a hydrate, an anhydride, or an aqueous solution. Specific examples of the alkali metal carboxylate include lithium acetate, sodium acetate, potassium acetate, sodium propionate, lithium valerate, sodium benzoate, sodium phenylacetate, potassium p-toluate, and mixtures thereof.

[0055] The alkali metal carboxylate may be formed by adding and reacting an organic acid with one or more compounds selected from the group consisting of alkali metal hydroxides, alkali metal carbonates, and alkali metal bicarbonates in approximately equal chemical equivalents. Among the above alkali metal carboxylates, lithium salts are preferred because they are expensive but have high solubility in the reaction system and a large auxiliary effect. Potassium, rubidium, and cesium salts may have slightly low solubility in the reaction system, but are preferred because they are inexpensive. Sodium acetate is the most preferred from the standpoint of a balance between moderate solubility in the polymerization system, auxiliary effect, and price.

[0056] When these alkali metal carboxylates are used as polymerization aids, the amount used is usually preferably in the range of 0.01 mol to 2 mol per mol of the charged alkali metal sulfide, and in terms of obtaining a higher degree of polymerization, the range of 0.1 to 0.6 mol is more preferable, and the range of 0.2 to 0.5 mol is even more preferable.

[0057] When water is used as a polymerization aid, the amount used is usually preferably in the range of 0.3 mol to 15 mol per mol of the charged alkali metal sulfide, more preferably in the range of 0.6 to 10 mol, and even more preferably in the range of 1 to 5 mol, in terms of obtaining a higher degree of polymerization.

[0058] Of course, two or more of these polymerization aids can be used in combination. For example, the combination of an alkali metal carboxylate and water allows for a higher molecular weight with a smaller amount of each.

[0059] There is no particular designation for the timing of addition of these polymerization aids, and they may be added at any time during the pre-step, at the start of polymerization, or during the polymerization, as described below, or may be added in several batches. When an alkali metal carboxylate is used as the polymerization aid, it is more preferable to add it at the start of the pre-step or at the start of polymerization, since it is easy to add it. When water is used as the polymerization aid, it is effective to add it during the polymerization reaction after the polyhalogenated aromatic compound is charged.

[0060] [Polymerization stabilizer] A polymerization stabilizer can be used to stabilize the polymerization reaction system and prevent side reactions. The polymerization stabilizer contributes to the stabilization of the polymerization reaction system and suppresses undesirable side reactions. One indicator of side reactions is the generation of thiophenol, and the addition of a polymerization stabilizer can suppress the generation of thiophenol. Specific examples of polymerization stabilizers include compounds such as alkali metal hydroxides, alkali metal carbonates, alkaline earth metal hydroxides, and alkaline earth metal carbonates. Among these, alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide are preferred. The above-mentioned alkali metal carboxylates also act as polymerization stabilizers, and therefore are included in the polymerization stabilizers. In addition, when an alkali metal hydrosulfide is used as a sulfidizing agent, it is particularly preferable to use an alkali metal hydroxide at the same time, as mentioned above, but an excess of an alkali metal hydroxide relative to the sulfidizing agent can also serve as a polymerization stabilizer.

[0061] These polymerization stabilizers can be used alone or in combination of two or more. The amount of polymerization stabilizer used is usually preferably 0.02 to 0.2 mol, more preferably 0.03 to 0.1 mol, and even more preferably 0.04 to 0.09 mol, per mol of the charged alkali metal sulfide. When the amount used is 0.02 mol or more, a sufficient stabilizing effect is easily obtained. Also, when the amount used is 0.2 mol or less, it is economically advantageous and tends to improve the polymer yield.

[0062] The timing of adding the polymerization stabilizer is not particularly specified, and it may be added at any time during the pre-step described below, at the start of polymerization, or during the polymerization, or may be added in several divided portions. However, it is more preferable to add it simultaneously at the start of the pre-step or at the start of polymerization from the viewpoint of ease.

[0063] Next, a preferred method for producing the PPS resin used in the present invention will be specifically described in order, including a pre-process, a polymerization reaction process, a recovery process, and a post-treatment process, although the present invention is not limited to this method.

[0064] [Pre-process] In the production method for PPS resin, the sulfidizing agent is usually used in the form of a hydrate, and it is preferable to heat the mixture containing the organic polar solvent and the sulfidizing agent and remove excess water from the system before adding the polyhalogenated aromatic compound.

[0065] As described above, the sulfidizing agent may be prepared in situ in the reaction system from an alkali metal hydrosulfide and an alkali metal hydroxide, or in a tank separate from the polymerization tank. There is no particular restriction on this method, but a preferable method is to add an alkali metal hydrosulfide and an alkali metal hydroxide to an organic polar solvent in an inert gas atmosphere at room temperature to 150°C, preferably from room temperature to 100°C, and then heat the mixture to at least 150°C or higher, preferably 180 to 260°C, under normal pressure or reduced pressure, to distill off water. A polymerization aid may be added at this stage. Toluene or the like may be added to promote the distillation of water.

[0066] In the polymerization reaction, the amount of water in the polymerization system is preferably 0.3 to 10.0 mol per 1 mol of the charged sulfidizing agent. Here, the amount of water in the polymerization system is the amount of water charged to the polymerization system minus the amount of water removed from the polymerization system. The charged water may be in any form such as water, an aqueous solution, or crystal water.

[0067] [Polymerization reaction process] The PPS resin is produced by reacting a sulfidizing agent with a polyhalogenated aromatic compound in an organic polar solvent at a temperature range of 200°C or higher and lower than 290°C.

[0068] When starting the polymerization reaction process, the organic polar solvent, the sulfidizing agent, and the polyhalogenated aromatic compound are mixed, desirably in an inert gas atmosphere, at a temperature range of room temperature to 240° C., preferably 100 to 230° C. A polymerization aid may be added at this stage. The order of charging these raw materials may be random, or they may be charged simultaneously.

[0069] The mixture is usually heated to a temperature in the range of 200° C. to 290° C. There are no particular limitations on the heating rate, but a rate of 0.01 to 5° C. / min is usually selected, and a range of 0.1 to 3° C. / min is more preferable.

[0070] In general, the temperature is finally raised to 250 to 290° C., and the reaction is carried out at that temperature for usually 0.25 to 50 hours, preferably 0.5 to 20 hours.

[0071] In order to obtain a higher degree of polymerization, it is effective to react at 200° C. to 260° C. for a certain period of time before the final temperature is reached, and then to raise the temperature to 270° C. to 290° C. In this case, the reaction time at 200° C. to 260° C. is usually selected within the range of 0.25 hours to 20 hours, and preferably 0.25 hours to 10 hours.

[0072] In order to obtain a polymer with a higher degree of polymerization, it may be effective to carry out the polymerization in multiple stages. When carrying out the polymerization in multiple stages, it is effective to carry out the polymerization when the conversion rate of the polyhalogenated aromatic compound in the system at 245°C reaches 40 mol% or more, preferably 60 mol%.

[0073] The conversion rate of polyhalogenated aromatic compounds (abbreviated as PHA here) is a value calculated by the following formulas (a) and (b). The amount of remaining PHA can usually be determined by gas chromatography.

[0074] (A) When a polyhalogenated aromatic compound is added in excess of an alkali metal sulfide in terms of molar ratio Conversion rate = [PHA charge amount (mol) - PHA remaining amount (mol)] / [PHA charge amount (mol) - PHA excess amount (mol)] (a) (B) Cases other than (A) above Conversion rate = [PHA charge amount (mol) - PHA remaining amount (mol)] / [PHA charge amount (mol)] (b) [Recovery process] In the method for producing a PPS resin, after the polymerization is completed, a solid matter is recovered from a polymerization reaction product containing a polymer, a solvent, etc. As the recovery method, any known method may be adopted.

[0075] For example, after the polymerization reaction is completed, the polymer particles may be collected by gradually cooling the mixture. The cooling rate is not particularly limited, but is usually about 0.1°C / min to 3°C / min. It is not necessary to cool the mixture at the same rate throughout the entire cooling process, and the mixture may be cooled at a rate of 0.1 to 1°C / min until the polymer particles crystallize and precipitate, and then at a rate of 1°C / min or more.

[0076] It is also preferred to carry out the above recovery under rapid cooling conditions, and a preferred recovery method is the flash method. In the flash method, the polymerization reaction product is subjected to high temperature and high pressure (usually 250°C or higher, 8 kg / cm 2 The method is to flash the polymer from the above state into an atmosphere of normal pressure or reduced pressure, recover the solvent, and recover the polymer in powder form at the same time. Flashing here means to eject the polymerization reaction product from a nozzle. Specific examples of the flashing atmosphere include nitrogen or water vapor at normal pressure, and the temperature is usually selected in the range of 150°C to 250°C.

[0077] [Post-processing process] The PPS resin may be produced through the above-mentioned polymerization and recovery steps, and then subjected to acid treatment, hot water treatment, washing with an organic solvent, or alkali metal or alkaline earth metal treatment.

[0078] The acid treatment is carried out as follows. There are no particular limitations on the acid used in the acid treatment of the PPS resin, so long as it does not have the effect of decomposing the PPS resin, and examples of the acid include acetic acid, hydrochloric acid, sulfuric acid, phosphoric acid, silicic acid, carbonic acid, and propylic acid. Of these, acetic acid and hydrochloric acid are more preferably used. Acids that decompose and deteriorate the PPS resin, such as nitric acid, are not preferred.

[0079] The acid treatment may be carried out, for example, by immersing the PPS resin in an acid or an aqueous solution of an acid. Stirring or heating may be carried out as necessary. For example, when acetic acid is used, a sufficient effect can be obtained by immersing the PPS resin powder in an aqueous solution of pH 4 heated to 80 to 200°C and stirring for 30 minutes. The pH after the treatment may be 4 or higher, for example, about pH 4 to 8. The PPS resin that has been subjected to the acid treatment is preferably washed several times with water or warm water to remove the remaining acid or salt. The water used for washing is preferably distilled water or deionized water in the sense that it does not impair the effect of the preferable chemical modification of the PPS resin by the acid treatment.

[0080] The hot water treatment is carried out as follows: When treating the PPS resin with hot water, the temperature of the hot water is preferably 100° C. or higher, more preferably 120° C. or higher, even more preferably 150° C. or higher, and particularly preferably 170° C. or higher. Temperatures below 100° C. are not preferred because the desired chemical modification effect of the PPS resin is small.

[0081] In order to achieve the desired chemical modification effect of the PPS resin by the hot water treatment, it is preferable that the water used is distilled water or deionized water. There is no particular limitation on the operation of the hot water treatment, and it can be carried out, for example, by putting a predetermined amount of PPS resin into a predetermined amount of water, heating and stirring in a pressure vessel, or by continuously carrying out hot water treatment. The ratio of PPS resin to water is preferably higher, but a bath ratio of 200 g or less of PPS resin per 1 liter of water is usually selected.

[0082] In addition, the treatment is preferably performed in an inert atmosphere to avoid decomposition of the terminal groups. Furthermore, after this hot water treatment, the PPS resin is preferably washed several times with warm water to remove any remaining components.

[0083] When washing with an organic solvent is performed, the procedure is as follows. The organic solvent used for washing the PPS resin is not particularly limited as long as it does not have the action of decomposing the PPS resin. Examples of the organic solvent include nitrogen-containing polar solvents such as N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, 1,3-dimethylimidazolidinone, hexamethylphosphoramide, and piperazinones; sulfoxide and sulfone solvents such as dimethyl sulfoxide, dimethyl sulfone, and sulfolane; ketone solvents such as acetone, methyl ethyl ketone, diethyl ketone, and acetophenone; ether solvents such as dimethyl ether, dipropyl ether, dioxane, and tetrahydrofuran; halogen-based solvents such as chloroform, methylene chloride, trichloroethylene, ethylene dichloride, perchloroethylene, monochloroethane, dichloroethane, tetrachloroethane, perchloroethane, and chlorobenzene; alcohol and phenol solvents such as methanol, ethanol, propanol, butanol, pentanol, ethylene glycol, propylene glycol, phenol, cresol, polyethylene glycol, and polypropylene glycol; and aromatic hydrocarbon solvents such as benzene, toluene, and xylene. Among these organic solvents, N-methyl-2-pyrrolidone, acetone, dimethylformamide and chloroform are particularly preferred. These organic solvents may be used alone or in combination of two or more.

[0084] The washing method using an organic solvent may be, for example, a method of immersing the PPS resin in the organic solvent. Stirring or heating may be performed as necessary. There is no particular restriction on the washing temperature when washing the PPS resin with an organic solvent, and any temperature between room temperature and about 300°C may be selected. The higher the washing temperature, the higher the washing efficiency tends to be, but usually a washing temperature between room temperature and 150°C is sufficient to obtain the desired effect. Washing may also be performed under pressure in a pressure vessel at a temperature equal to or higher than the boiling point of the organic solvent. There is also no particular restriction on the washing time. Although it depends on the washing conditions, in the case of batch washing, washing for 5 minutes or more usually provides a sufficient effect. Continuous washing is also possible.

[0085] The alkali metal or alkaline earth metal treatment is carried out as follows. Examples of the method of alkali metal or alkaline earth metal treatment include a method of adding an alkali metal salt or an alkaline earth metal salt before, during or after the previous step, a method of adding an alkali metal salt or an alkaline earth metal salt into a polymerization vessel before, during or after the polymerization step, or a method of adding an alkali metal salt or an alkaline earth metal salt at the beginning, middle or end of the washing step. The easiest method among them is a method of adding an alkali metal salt or an alkaline earth metal salt after removing residual oligomers or residual salts by washing with an organic solvent or washing with warm or hot water. The alkali metal or alkaline earth metal is preferably introduced into the PPS resin in the form of an alkali metal ion or an alkaline earth metal ion such as an acetate, hydroxide or carbonate. It is also preferable to remove excess alkali metal salt or alkaline earth metal salt by washing with warm water or the like. The concentration of the alkali metal ion or alkaline earth metal ion when introducing the alkali metal or alkaline earth metal is preferably 0.001 to 0.07 mmol, and more preferably 0.01 to 0.05 mmol, per 1 g of PPS resin. The temperature is preferably 50° C. or higher, more preferably 75° C. or higher, and particularly preferably 90° C. or higher. There is no particular upper limit to the temperature, but from the viewpoint of operability, 280° C. is usually preferred. The bath ratio (weight of cleaning solution relative to weight of dry PPS resin) is preferably 0.5 or higher, more preferably 3 or higher, and even more preferably 5 or higher.

[0086] In addition, the PPS resin can be used after being polymerized by a thermal oxidative crosslinking treatment, which involves heating in an oxygen atmosphere after polymerization or by heating with the addition of a crosslinking agent such as a peroxide.

[0087] When dry heat treatment is performed for the purpose of increasing the molecular weight by thermal oxidation crosslinking, the temperature is preferably 160 to 260°C, more preferably 170 to 250°C. The oxygen concentration is desirably 5% by volume or more, more desirably 8% by volume or more. There is no particular upper limit to the oxygen concentration, but the limit is about 50% by volume. The treatment time is preferably 0.5 to 100 hours, more preferably 1 to 50 hours, and even more preferably 2 to 25 hours. The heat treatment device may be a normal hot air dryer or a rotary or stirring blade-equipped heating device, but it is more preferable to use a rotary or stirring blade-equipped heating device in terms of efficient and more uniform treatment.

[0088] It is also possible to perform a dry heat treatment for the purpose of suppressing thermal oxidative crosslinking and removing volatile matter. The temperature is preferably 130 to 250°C, more preferably 160 to 250°C. In this case, the oxygen concentration is preferably less than 5% by volume, and even more preferably less than 2% by volume. The treatment time is preferably 0.5 to 50 hours, more preferably 1 to 20 hours, and even more preferably 1 to 10 hours. The heat treatment device may be a normal hot air dryer or a rotary or stirring blade-equipped heating device, but it is more preferable to use a rotary or stirring blade-equipped heating device in terms of efficient and more uniform treatment.

[0089] However, from the viewpoint of exhibiting excellent toughness, the PPS resin is preferably a substantially linear PPS resin that has not been subjected to a thermal oxidative crosslinking treatment to increase the molecular weight, or a semi-crosslinked PPS resin that has been subjected to a light oxidative crosslinking treatment. In the present invention, a mixture of multiple PPS resins having different melt viscosities may be used.

[0090] <Method for producing fiber-reinforced thermoplastic resin substrate> The fiber-reinforced thermoplastic resin substrate of the present invention can be obtained by impregnating continuous reinforcing fibers with a PPS resin.

[0091] Examples of methods for impregnating continuous reinforcing fibers with PPS resin include the film method in which a film-like PPS resin is melted and pressurized to impregnate a reinforcing fiber bundle with PPS resin, the comingle method in which a fibrous PPS resin is mixed with a reinforcing fiber bundle, and then the fibrous PPS resin is melted and pressurized to impregnate the reinforcing fiber bundle with a thermoplastic resin, the powder method in which a powdered PPS resin is dispersed in the gaps between the fibers in the reinforcing fiber bundle, and then the powdered PPS resin is melted and pressurized to impregnate the reinforcing fiber bundle with PPS resin, and the pultrusion method in which a reinforcing fiber bundle is immersed in molten PPS resin and pressurized to impregnate the reinforcing fiber bundle with PPS resin. Among these, the pultrusion method is preferred because it can produce a wide variety of fiber-reinforced thermoplastic resin substrates with various thicknesses and fiber volume contents.

[0092] The thickness of the fiber-reinforced thermoplastic resin substrate of the present invention is preferably 0.1 to 10 mm. If the thickness is 0.1 mm or more, the strength of a molded product obtained by using the fiber-reinforced thermoplastic resin substrate can be improved. The thickness is more preferably 0.2 mm or more. On the other hand, if the thickness is 1.5 mm or less, the reinforcing fibers can be more easily impregnated with the PPS resin. The thickness is more preferably 1 mm or less, further preferably 0.7 mm or less, and particularly preferably 0.6 mm or less.

[0093] In addition, the fiber reinforced thermoplastic resin substrate of the present invention preferably contains 20% by volume or more and 65% by volume or less of reinforcing fibers in 100% by volume of the entire fiber reinforced thermoplastic resin substrate. That is, the fiber reinforced thermoplastic resin substrate of the present invention preferably has a fiber volume content of 20 to 65% by volume. By having a fiber volume content of 20% by volume or more, the strength of a molded product obtained by using the fiber reinforced thermoplastic resin substrate can be further improved. The fiber volume content is more preferably 30% by volume or more, and even more preferably 40% by volume or more. On the other hand, by having a fiber volume content of 65% by volume or less, it is easier to impregnate the reinforcing fibers with thermoplastic. The fiber volume content is more preferably 60% by volume or less, and even more preferably 55% by volume or less. The fiber volume content can be adjusted to a desired range by adjusting the input amounts of the reinforcing fibers and the PPS resin.

[0094] The volume fraction (Vf) of the reinforcing fibers in the fiber-reinforced thermoplastic resin substrate is calculated by measuring the mass W0 of the fiber-reinforced thermoplastic resin substrate, heating the fiber-reinforced thermoplastic resin substrate in air at 500°C for 30 minutes to burn off the thermoplastic resin component, measuring the mass W1 of the remaining reinforcing fibers, and calculating the volume fraction (Vf) of the reinforcing fibers in the fiber-reinforced thermoplastic resin substrate using the following formula (c).

[0095] Vf (volume%) = (W1 / ρf) / {W1 / ρf+(W0-W1) / ρr}×100 (c) ρf: Density of reinforcing fiber (g / cm 3 ) ρr: Density of PPS resin (g / cm 3 ).

[0096] The fiber-reinforced thermoplastic resin substrate of the present invention is a fiber-reinforced thermoplastic resin substrate having excellent mechanical properties. As a guideline, the fiber-reinforced thermoplastic resin substrate of the present invention has a strength of preferably 130 to 200 MPa, more preferably 140 to 180 MPa in a 90° bending test of a molded piece according to ASTM D790. When the strength of the molded piece in a 90° bending test according to ASTM D790 is 130 MPa or more, the impact resistance and interlaminar shear strength of the fiber-reinforced thermoplastic resin substrate tend to be improved.

[0097] In addition, the fiber reinforced thermoplastic resin substrate of the present invention can be selected according to the desired impregnation property depending on its usage and purpose. For example, a prepreg with higher impregnation property, a semi-preg with half impregnation property, a fabric with low impregnation property, etc. are included. In general, a molding material with higher impregnation property is preferable because a molded product with excellent mechanical properties can be obtained by molding for a short time.

[0098] Examples of methods for applying heat and / or pressure include a press molding method in which a fiber-reinforced thermoplastic resin laminated in an arbitrary configuration is placed in a mold or on a press plate, and then the mold or press plate is closed to apply pressure, an autoclave molding method in which a molding material laminated in an arbitrary configuration is placed in an autoclave and pressurized and heated, a bagging molding method in which a molding material laminated in an arbitrary configuration is wrapped in a film or the like, and heated in an oven while reducing the internal pressure and applying pressure at atmospheric pressure, a wrapping tape method in which a fiber-reinforced thermoplastic resin laminated in an arbitrary configuration is wrapped in tape while applying tension and heated in an oven, and an internal pressure molding method in which a fiber-reinforced PPS resin laminated in an arbitrary configuration is placed in a mold, and a gas or liquid is injected into a core also placed in the mold to apply pressure, etc. In particular, a molding method using a mold for pressing is preferably used because it produces molded products with few voids in the molded product and excellent appearance quality.

[0099] As the press molding method, for example, a hot press method in which a fiber-reinforced thermoplastic resin substrate is placed in a mold in advance, pressurized and heated while the mold is closed, and then the mold is cooled to cool the fiber-reinforced thermoplastic resin substrate while the mold is still closed to obtain a molded product, or stamping molding, which is a method in which a fiber-reinforced thermoplastic resin substrate is heated in advance to a temperature higher than the melting temperature of the thermoplastic resin by a heating device such as a far-infrared heater, a heating plate, a high-temperature oven, or a dielectric heating device, the thermoplastic resin is placed on the mold that will become the lower surface of the molding die in a melted and softened state, the mold is then closed to perform mold clamping, and then pressurized and cooled, can be used. There are no particular limitations on the press molding method, but stamping molding is preferable from the viewpoint of accelerating the molding cycle and increasing productivity.

[0100] The fiber-reinforced thermoplastic resin substrate and molded product in the present invention can be subjected to integrated molding such as insert molding and outsert molding, or to a bonding method or adhesive having excellent productivity such as heat correction, heat welding, vibration welding, and ultrasonic welding. It is possible to obtain a composite.

[0101] A composite molded article in which the fiber-reinforced thermoplastic resin substrate in the present invention and a molded article containing a thermoplastic resin are at least partially bonded to each other is preferred.

[0102] The molded article (substrate for molding and molded article) containing the thermoplastic resin integrated with the fiber reinforced thermoplastic resin substrate in the present invention is not particularly limited, and examples thereof include resin materials and molded articles, metal materials and molded articles, inorganic materials and molded articles, etc. Among them, resin materials and molded articles are preferred in terms of adhesive strength with the fiber reinforced thermoplastic resin in the present invention.

[0103] The molding material and the matrix resin of the molded product integrated with the fiber reinforced thermoplastic resin substrate in the present invention may be the same type of resin as the fiber reinforced thermoplastic resin substrate and the molded product, or may be a different type of resin. In order to further increase the adhesive strength, it is preferable that the resin is the same type. In the case of a different type of resin, it is more preferable to provide a resin layer at the interface. EXAMPLES

[0104] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0105] In the examples and comparative examples, the following PPS resin and reinforcing fibers were used. [PPS resin] In the following Reference Examples 1 to 6, PPS-1 to PPS-6 were synthesized.

[0106] [Reference Example 1 (Synthesis of PPS-1)] A 70-liter autoclave equipped with a stirrer was charged with 8.27 kg of 47.5% sodium hydrosulfide, 2.96 kg of 96% sodium hydroxide, 11.43 kg of N-methyl-2-pyrrolidone (NMP), 2.58 kg of sodium acetate, and 10.5 kg of ion-exchanged water, and gradually heated to 245°C over approximately 3 hours under normal pressure while passing nitrogen through it. After distilling off 14.8 kg of water and 280 g of NMP, the reaction vessel was cooled to 160°C.

[0107] Next, 10.2 kg of p-dichlorobenzene, 22.5 g of 1,2,4-trichlorobenzene, and 9.00 kg of NMP were added, the reaction vessel was sealed under nitrogen gas, and the temperature was raised to 238°C at a rate of 0.6°C / min while stirring at 240 rpm. After 95 minutes of reaction at 238°C, the temperature was raised to 270°C at a rate of 0.8°C / min. After 150 minutes of reaction at 270°C, the mixture was cooled to 250°C at a rate of 1.3°C / min while injecting 1.26 kg of water over 15 minutes. The mixture was then cooled to 200°C at a rate of 1.0°C / min, and then rapidly cooled to near room temperature.

[0108] The contents were taken out, washed twice with 40.0 kg of NMP, and filtered. This was washed several times with 56.0 kg of ion-exchanged water, filtered, and then washed with 70.0 kg of 0.05 wt% acetic acid aqueous solution and filtered. After washing with 70.0 kg of ion-exchanged water and filtering, the obtained hydrous PPS particles were dried with hot air at 80°C and dried under reduced pressure at 120°C. The obtained PPS-1 had a weight average molecular weight of 79,000, an ash content of 0.01 wt%, and a carboxyl group content of 10 μmol / g.

[0109] [Reference Example 2 (Synthesis of PPS-2)] A 70-liter autoclave equipped with a stirrer was charged with 8.27 kg of 47.5% sodium hydrosulfide, 2.96 kg of 96% sodium hydroxide, 11.43 kg of N-methyl-2-pyrrolidone (NMP), 2.58 kg of sodium acetate, and 10.5 kg of ion-exchanged water, and gradually heated to 245°C over approximately 3 hours under normal pressure while passing nitrogen through it. After distilling off 14.8 kg of water and 280 g of NMP, the reaction vessel was cooled to 160°C.

[0110] Next, 10.2 kg of p-dichlorobenzene and 9.00 kg of NMP were added, the reaction vessel was sealed under nitrogen gas, and the temperature was raised to 238°C at a rate of 0.6°C / min while stirring at 240 rpm. After 95 minutes of reaction at 238°C, the temperature was raised to 270°C at a rate of 0.8°C / min. After 150 minutes of reaction at 270°C, the mixture was cooled to 250°C at a rate of 1.3°C / min while injecting 1.26 kg of water over 15 minutes. The mixture was then cooled to 200°C at a rate of 1.0°C / min, and then quenched to near room temperature.

[0111] The contents were taken out, washed twice with 40.0 kg of NMP, and filtered. This was washed several times with 56.0 kg of ion-exchanged water, filtered, and then washed with 70.0 kg of 0.05 wt% acetic acid aqueous solution and filtered. After washing with 70.0 kg of ion-exchanged water and filtering, the obtained hydrous PPS particles were dried with hot air at 80°C and dried under reduced pressure at 120°C. The obtained PPS-2 had a weight average molecular weight of 75,500, an ash content of 0.10 wt%, and a carboxyl group content of 18 μmol / g.

[0112] [Reference Example 3 (Synthesis of PPS-3)] A 70-liter autoclave equipped with a stirrer was charged with 8.27 kg of 47.5% sodium hydrosulfide, 2.96 kg of 96% sodium hydroxide, 11.43 kg of N-methyl-2-pyrrolidone (NMP), 2.58 kg of sodium acetate, and 10.5 kg of ion-exchanged water, and gradually heated to 245°C over approximately 3 hours under normal pressure while passing nitrogen through it. After distilling off 14.8 kg of water and 280 g of NMP, the reaction vessel was cooled to 160°C.

[0113] Next, 10.2 kg of p-dichlorobenzene and 9.00 kg of NMP were added, the reaction vessel was sealed under nitrogen gas, and the temperature was raised to 238°C at a rate of 0.6°C / min while stirring at 240 rpm. After 95 minutes of reaction at 238°C, the temperature was raised to 270°C at a rate of 0.8°C / min. After 200 minutes of reaction at 270°C, the mixture was cooled to 250°C at a rate of 1.3°C / min while injecting 1.26 kg of water over 15 minutes. The mixture was then cooled to 200°C at a rate of 1.0°C / min, and then quenched to near room temperature.

[0114] The contents were taken out, washed twice with 30.0 kg of NMP, and filtered. This was washed several times with 56.0 kg of ion-exchanged water, filtered, and then washed with 70.0 kg of 0.05 wt% acetic acid aqueous solution and filtered. After washing with 70.0 kg of ion-exchanged water and filtering, the obtained hydrous PPS particles were dried with hot air at 80°C and dried under reduced pressure at 120°C. The obtained PPS-3 had a weight average molecular weight of 78,000, an ash content of 0.01 wt%, and a carboxyl group content of 10 μmol / g.

[0115] [Reference Example 4 (Synthesis of PPS-4)] A 70-liter autoclave equipped with a stirrer was charged with 8.27 kg of 47.5% sodium hydrosulfide, 2.96 kg of 96% sodium hydroxide, 11.43 kg of N-methyl-2-pyrrolidone (NMP), 2.58 kg of sodium acetate, and 10.5 kg of ion-exchanged water, and gradually heated to 245°C over approximately 3 hours under normal pressure while passing nitrogen through it. After distilling off 14.8 kg of water and 280 g of NMP, the reaction vessel was cooled to 160°C.

[0116] Next, 10.2 kg of p-dichlorobenzene and 90.0 kg of NMP were added, the reaction vessel was sealed under nitrogen gas, and the temperature was raised to 238°C at a rate of 0.6°C / min while stirring at 240 rpm. After 95 minutes of reaction at 238°C, the temperature was raised to 270°C at a rate of 0.8°C / min. After 100 minutes of reaction at 270°C, the mixture was cooled to 250°C at a rate of 1.3°C / min while injecting 1.26 kg of water over 15 minutes. The mixture was then cooled to 200°C at a rate of 1.0°C / min, and then quenched to near room temperature.

[0117] The contents were taken out, washed twice with 30.0 kg of NMP, and filtered. This was washed several times with 56.0 kg of ion-exchanged water, filtered, and then washed with 70.0 kg of 0.05 wt% acetic acid aqueous solution and filtered. After washing with 70.0 kg of ion-exchanged water and filtering, the obtained hydrous PPS particles were dried with hot air at 80°C and dried under reduced pressure at 120°C. The obtained PPS-4 had a weight average molecular weight of 72000, an ash content of 0.01 wt%, and a carboxyl group content of 30 μmol / g.

[0118] [Reference Example 5 (Synthesis of PPS-5)] A 70-liter autoclave equipped with a stirrer was charged with 8.27 kg of 47.5% sodium hydrosulfide, 2.96 kg of 96% sodium hydroxide, 11.43 kg of N-methyl-2-pyrrolidone (NMP), 2.58 kg of sodium acetate, and 10.5 kg of ion-exchanged water, and gradually heated to 245°C over approximately 3 hours under normal pressure while passing nitrogen through it. After distilling off 14.8 kg of water and 280 g of NMP, the reaction vessel was cooled to 160°C.

[0119] Next, 10.2 kg of p-dichlorobenzene and 90.0 kg of NMP were added, the reaction vessel was sealed under nitrogen gas, and the temperature was raised to 238°C at a rate of 0.6°C / min while stirring at 240 rpm. After 95 minutes of reaction at 238°C, the temperature was raised to 270°C at a rate of 0.8°C / min. After 200 minutes of reaction at 270°C, the mixture was cooled to 250°C at a rate of 1.3°C / min while injecting 1.26 kg of water over 15 minutes. The mixture was then cooled to 200°C at a rate of 1.0°C / min, and then quenched to near room temperature.

[0120] The contents were taken out, washed twice with 30.0 kg of NMP, and filtered. The particles were washed several times with 56.0 kg of ion-exchanged water, and filtered to obtain undried PPS particles. 20 kg of the undried PPS resin and 110 g of calcium acetate monohydrate were added to 200 kg of ion-exchanged water, stirred at 70°C for 30 minutes, and then filtered to separate the solid and liquid. 20 kg of ion-exchanged water was added to the obtained solid, stirred at 70°C for 30 minutes, and then filtered to recover the solid. The solid thus obtained was dried at 120°C under a nitrogen stream. The resulting PPS-5 had a weight average molecular weight of 65,800, an ash content of 0.30% by weight, and a carboxyl group content of 0 μmol / g.

[0121] [Reference Example 6 (Synthesis of PPS-6)] A 70-liter autoclave equipped with a stirrer was charged with 8.27 kg of 47.5% sodium hydrosulfide, 2.96 kg of 96% sodium hydroxide, 11.43 kg of N-methyl-2-pyrrolidone (NMP), 2.58 kg of sodium acetate, and 10.5 kg of ion-exchanged water, and gradually heated to 245°C over approximately 3 hours under normal pressure while passing nitrogen through it. After distilling off 14.8 kg of water and 280 g of NMP, the reaction vessel was cooled to 160°C.

[0122] Next, 10.2 kg of p-dichlorobenzene and 90.0 kg of NMP were added, the reaction vessel was sealed under nitrogen gas, and the temperature was raised to 238°C at a rate of 0.6°C / min while stirring at 240 rpm. After 95 minutes of reaction at 238°C, the temperature was raised to 270°C at a rate of 0.8°C / min. After 200 minutes of reaction at 270°C, the mixture was cooled to 250°C at a rate of 1.3°C / min while injecting 1.26k water over 15 minutes. The mixture was then cooled to 200°C at a rate of 1.0°C / min, and then quenched to near room temperature.

[0123] The contents were taken out, washed twice with 40.0 kg of NMP, and filtered. The particles were washed several times with 56.0 kg of ion-exchanged water, and filtered to obtain undried PPS particles. 20 kg of the obtained undried PPS resin and 110 g of calcium acetate monohydrate were added to 200 kg of ion-exchanged water, stirred at 70 ° C for 30 minutes, and then filtered to separate the solid and liquid. 20 kg of ion-exchanged water was added to the obtained solid, stirred at 70 ° C for 30 minutes, and then filtered to recover the solid. The solid thus obtained was dried at 120 ° C under a nitrogen stream. The obtained PPS-6 had a weight average molecular weight of 80,000, an ash content of 0.30 wt%, and a carboxyl group content of 0 μmol / g.

[0124] [Reinforced fiber] CF-1: Carbon fiber bundle (Toray Industries, Inc., product name T700S-12K) [Weight average molecular weight of PPS resin] The weight average molecular weight (Mw) of the PPS resin was calculated in terms of polystyrene using gel permeation chromatography (GPC). The GPC measurement conditions are shown below.

[0125] Equipment: SSC-7110 (Senshu Science) Column name: Shodex UT806M x 2 Eluent: 1-chloronaphthalene Detector: Differential refractive index detector Column temperature: 210℃ Pre-thermostat temperature: 250℃ Pump thermostatic chamber temperature: 50℃ Detector temperature: 210℃ Flow rate: 1.0mL / min Sample injection volume: 300 μL (slurry: approximately 0.2% by weight).

[0126] [Carboxyl group content of PPS resin] The carboxyl group content of the PPS resin was calculated using a Fourier transform infrared spectrometer (hereinafter abbreviated as FT-IR).

[0127] First, benzoic acid was measured as a standard substance by FT-IR, and the absorption of the C-H bond of the benzene ring at 3066 cm -1 The absorption intensity of the peak (b1) and the absorption of the carboxyl group at 1704 cm -1 The absorption intensity (c1) of the peak was read, and the carboxyl group content (U1) per benzene ring unit, (U1) = (c1) / [(b1) / 5], was calculated. Next, the PPS resin was melt-pressed at 320°C for 1 minute, and then quenched to obtain an amorphous film, which was then subjected to FT-IR measurement. -1 Absorption intensity (b2) and 1704cm -1 The absorption intensity (c2) of the sample was read, and the carboxyl group content per benzene ring unit (U2), (U2) = (c2) / [(b2) / 4], was calculated. The carboxyl group content per 1 g of PPS resin was calculated from the following formula (d). Carboxyl group content of PPS resin (μmol / g) = (U2) / (U1) / 108.161 × 1000000 (d) [Ash content] Five grams of the sample was weighed out and placed in a crucible that had been preheated at 550°C, and then incinerated in an electric furnace at 550°C for 24 hours. The weight of the ash remaining in the crucible was weighed out, and the ratio of the weight of the sample before incineration was calculated as the ash content (wt%).

[0128] [Measurement of fiber volume fraction (Vf)] The fiber volume content of the fiber reinforced thermoplastic resin substrate was determined by measuring the mass W0 of the fiber reinforced thermoplastic resin substrate, then eluting the PPS resin from the fiber reinforced thermoplastic resin substrate with 1-chloronaphthalene, measuring the mass W1 of the remaining reinforcing fibers after drying, and calculating the volume content (Vf) of the fiber reinforced thermoplastic resin substrate by the following formula (c).

[0129] Vf (volume%) = (W1 / ρf) / {W1 / ρf+(W0-W1) / ρr}×100 (c) ρf: Density of reinforcing fiber (g / cm 3 ) ρr: Density of PPS resin (g / cm 3 ) [Mechanical properties of molded specimens (90° bending test)] The fiber-reinforced thermoplastic resin substrates (width 50 mm × thickness 0.08 mm, unidirectional substrate) obtained from each Example and Comparative Example were laminated and press molded in the 0° direction to a thickness of 2.0 mm × width 100 mm × length 250 mm to obtain fiber-reinforced resin molded products. These molded products were cut into rectangular shapes of width 15 mm × length 125 mm × thickness 2.0 mm to obtain molded pieces for bending test measurement. The molded pieces were subjected to bending tests (n=5 each) in accordance with ASTM D790. It should be noted that the higher the 90° bending strength value, the more excellent the mechanical properties of the composite material.

[0130] [Examples 1 to 3, Comparative Examples 1 to 3] The pultrusion process was carried out by pulling strands (16 strands) of carbon fiber (T700S-12K) through an aqueous slurry of PPS. The aqueous slurry was formulated with 11.0 kg of PPS resin, which had been ground and powdered by air milling, 16.0 kg of ion-exchanged water, and 11.3 g of surfactant (ethoxylated octylphenol). The fibers were coated with the PPS resin from the aqueous slurry and then pulled through a die heated to 370°C to melt or soften the PPS resin. The carbon fibers were then completely impregnated with the PPS resin to obtain a fiber-reinforced thermoplastic resin substrate.

[0131] The obtained fiber-reinforced thermoplastic resin substrate had a thickness of 0.08 mm, a width of 50 mm, the reinforcing fibers were aligned in one direction, and the volume content was 60%. The obtained fiber-reinforced thermoplastic resin substrate was subjected to the above-mentioned evaluation. The evaluation results are shown in Table 1.

[0132] [Table 1]

[0133] The results of Examples 1 to 3 and Comparative Examples 1 to 3 will be compared and explained.

[0134] As shown in Table 1, the fiber-reinforced thermoplastic resin substrates of Examples 1 to 3 have extremely excellent 90° bending strength.

[0135] On the other hand, as shown in Table 1, in the case of the fiber-reinforced thermoplastic resin substrate of Comparative Example 1 using PPS (PPS-4) whose weight-average molecular weight is outside the range of the present invention, the 90° bending strength was low, less than 130 MPa. In addition, in the case of the fiber-reinforced thermoplastic resin substrate of Comparative Example 2 using PPS (PPS-5) whose weight-average molecular weight and ash content are outside the range of the present invention, the 90° bending strength was particularly low, 63 MPa. In the case of the fiber-reinforced thermoplastic resin substrate of Comparative Example 3 using PPS (PPS-6) whose ash content is outside the range of the present invention, the 90° bending strength was improved compared to Comparative Example 2, but was 78 MPa, less than 130 MPa. [Industrial Applicability]

[0136] The fiber-reinforced thermoplastic resin substrate and its molded article of the present invention can be utilized for various applications such as aircraft parts, automobile parts, electric and electronic parts, building materials, various containers, daily necessities, household goods, and sanitary products, taking advantage of their excellent properties. The fiber-reinforced thermoplastic resin substrate and its molded article of the present invention are particularly preferably used for applications requiring impregnation properties, heat aging resistance, and surface appearance, such as aircraft engine peripheral parts, aircraft parts exterior parts, automobile body parts vehicle frames, automobile engine peripheral parts, automobile underhood parts, automobile gear parts, automobile interior parts, automobile exterior parts, intake and exhaust system parts, engine cooling water system parts, automobile electrical parts, and electrical and electronic parts. Specifically, the fiber-reinforced thermoplastic resin substrate of the present invention and its molded article can be used in a wide variety of applications, including aircraft engine peripheral parts such as fan blades, aircraft-related parts such as landing gear pods, winglets, spoilers, edges, ladders, elevators, failings, and ribs, automobile body parts such as various seats, front bodies, underbodies, various pillars, various members, various frames, various beams, various supports, various rails, and various hinges, automobile engine peripheral parts such as engine covers, air intake pipes, timing belt covers, intake manifolds, filler caps, throttle bodies, and cooling fans, automobile engine parts such as cooling fans, radiator tank tops and bases, cylinder head covers, oil pans, brake piping, fuel piping tubes, and exhaust gas system parts. Automotive underhood parts, gears, actuators, bearing retainers, bearing cages, chain guides, chain tensioners and other automotive gear parts, shift lever brackets, steering lock brackets, key cylinders, door inner handles, door handle cowls, interior mirror brackets, air conditioner switches, instrument panels, console boxes, glove boxes, steering wheels, trim and other automotive interior parts, front fenders, rear fenders, fuel lids, door panels, cylinder head covers, door mirror stays, tailgate panels, license garnishes, roof rails, engine mount brackets, rear garnishes, rear spoilers, trunk lids, rocker moldings, moldings, lamp housings, front grilles,Automotive exterior parts such as mudguards and side bumpers; intake and exhaust system parts such as air intake manifolds, intercooler inlets, turbochargers, exhaust pipe covers, inner bushes, bearing retainers, engine mounts, engine head covers, resonators, and throttle bodies; engine coolant system parts such as chain covers, thermostat housings, outlet pipes, radiator tanks, oil inators, and delivery pipes; automotive electrical parts such as connectors, wire harness connectors, motor parts, lamp sockets, sensor in-vehicle switches, and combination switches; and electrical and electronic parts such as generators, electric motors, transformers, current transformers, voltage regulators, rectifiers, resistors, inverters, relays, power contacts, switches, circuit breakers, switches, knife switches, multi-pole rods, motor cases, television housings, notebook computer housings and internal parts, and CRT display housings and internal parts. , printer housings and internal parts, mobile terminal housings and internal parts for mobile phones, mobile personal computers, handheld mobile phones, etc., IC and LED housings, capacitor seat plates, fuse holders, various gears, various cases, electrical parts such as cabinets, connectors, SMT connectors, card connectors, jacks, coils, coil bobbins, sensors, LED lamps, sockets, resistors, relays, relay cases, reflectors, small switches, power supply parts, coil bobbins, capacitors, variable capacitor cases, optical pickup chassis, oscillators, various terminal boards, transformers, plugs, printed circuit boards, tuners, speakers, microphones, headphones, small motors, magnetic head bases, power modules, Si power modules and SiC power modules, semiconductors, liquid crystal, FDD carriages, FDD chassis, motor brush holders, transformer members, parabolic antennas, computer-related parts, and other electronic parts.

Claims

1. A fiber-reinforced thermoplastic resin substrate in which a plurality of continuous reinforcing fibers are impregnated with polyphenylene sulfide resin, wherein the weight average molecular weight of the polyphenylene sulfide resin is 75,000 to 150,000, the ash content of the polyphenylene sulfide resin is 0.001% by weight to 0.30% by weight, the carboxyl group content is 5 μmol / g to 25 μmol / g, and the fiber volume content is 20 to 65% by volume. The fiber-reinforced thermoplastic resin substrate.

2. The fiber reinforced thermoplastic resin substrate according to claim 1, wherein the ash content of the polyphenylene sulfide resin is 0.001% by weight or more and 0.25% by weight or less.

3. The fiber reinforced thermoplastic resin substrate according to claim 1 or 2, wherein the 90 ° flexural strength measured by a 90 ° bending test of a molded piece in accordance with ASTM D790 is 130 to 200 MPa.

Citation Information

Patent Citations

  • JP1477262B

  • Manufacture of polymeric composite material

    JP1990180934A

  • Thermoplastic poly (allylenesulfide) composite material

    JP1991292335A

  • Fiber-reinforced composite material

    JP1997025346A

  • Fiber-reinforced composite material and method for producing the same

    JP2010163552A